D-Psicose intake exacerbates dextran sulfate sodium-induced colitis in mice through alteration in the gut microbiota and dysfunction of mucosal barrier - Xuejiao Zhang; Ang Li; Yuanyifei Wang; Jin Wang; Bowei Zhang; Yan Zhang; Jingmin Liu; Shuo Wang (Food Science and Human Wellness)
D-Psicose, as a low-calorie rare sugar, has attracted a lot of attention in recent years for alternating to sucrose. The anti-obesity effect of D-psicose has been extensively confirmed in previous studies, however, the impact of D-psicose on colitis remains vague. Here, we firstly evaluated the effect of the D-psicose prophylactic intervention on dextran sulfate sodium-induced colitis in C57BL/6 mice. The pathological symptoms, inflammatory cytokines levels, gut microbiota composition, short chain fatty acids (SCFAs) production and colonic barrier integrity were comprehensively evaluated. The results confirmed that D-psicose intervention aggravated colitis, characterized by the exacerbation of colon shortening, increase of colonic inflammatory infiltration, and marked exaltation of disease activity indices and IL-6, IL-1β and TNF-α levels. Further, the dysfunction of gut microbiota was identified in the psicose group. The abundance of pro-inflammatory bacteria Lachnospiraceae_NK4A136_group was significantly up-regulated while the abundance of probiotics Akkermansia and Lactobacillus were significantly down-regulated in the psicose group compared to the model group. Moreover, the production of SCFAs was suppressed in the psicose group, accompanied by a decrease in the level of mucin 2 (Muc-2). Collectively, the underlying mechanism of the exacerbation of colitis by D-psicose intervention might be attributed to microbiota dysfunction accompanied by the reduction of SCFAs, which leads to the damage of the mucosal barrier and the intensification of inflammatory invasion.